The questions of the operation of law in time while overcoming the gaps in legislation - Пушняк, О. В. (Theory and practice of jurisprudence, 2016)
The article analyses the ways of retention of the time parameters set for a particular legal norm while application of the latter for overcoming the gaps in legislation. The given issue is scrutinized for both common and exceptional parameters of the temporal operation of a norm as well as for the analogy in statute, analogy in law and subsidiary application of law.